Naturally Occurring Deletion of Lys 107 Does Not Alter Lipid Binding Affinity of Apolipoprotein A-I - Díaz Ludovico, Ivo (2020)
Human apolipoprotein A-I (apoA-I) is the major protein component of high-density lipoproteins (HDLs) that plays a pivotal role in lipoprotein metabolism. The deletion mutant Lys107del (ΔK107) it’s a natural variant of apoA-I (Wt) related to early atherosclerosis and hypertriglyceridemia in carriers. While this mutant has been extensively studied, little information exists on the structural and functional basis for this phenotype. To investigate if exists alterations in oligomeric states of ΔK107 that are involved in his pathogenicity, we used isolated BS3-crosslinked oligomers (XL-oligomer) to investigate its structure and functionality in comparison with the Wt. Fluorescence measurements in monomeric, dimeric, trimeric and tetrameric Wt apoA-I showed highly similar spectra indicating similar environments for Trp residues. ΔK107 exhibited a slight red shift, likely due to the Lys deletion near a Try residue, but also showed similar spectra in all oligomeric states. Upon incorporation into lipoprotein complexes, the same red shift has been observed in all oligomeric states of ΔK107. Native PAGE sizing of XL-oligomers and XL-oligomer-lipoprotein complexes showed a comparable distribution for both variants. All XL-oligomers form large (440-660KDa) lipoprotein complexes with DMPC; but not all could form the typical small (140KDa) lipoprotein complexes observed for uncrosslinked proteins. Native LDL (nLDL) binding assays showed no-differences between Wt and ΔK107 in the profile and the amount of protein bind to the LDL. ΔK107 has been previously proposed to alter LDL or VLDL lipolysis by binding to these lipoproteins and altering lipolysis. Our work shows that the physiological effects of the mutation are likely not related with both their capacity to form Wt-same size oligomers or the capacity to interact with lipids.